An Overview of Criminal Laws in India in Relation to Sex and Sexuality - Choudhary Laxmi Narayan; Mridula Narayan; Kritika Agarwal; Lavanya Seth; Mridul Deepanshu (Journal of Psychosexual Health, 2023)
Sex and sexuality are frequently the cause of erratic, aggressive and violent behavior. Women are often at the receiving end of such behaviors and are subjected to sexual assaults. The Mathura rape case, the Nirbhaya case and the Kathua rape case are some of the heinous crime cases against women that occurred and rocked the entire country. In response to these cases, amendments were introduced in the laws dealing with the offences against women in our country by way of Criminal Law (Amendment) Acts in 1983, 2013 and 2018. Verma Committee formed after the Nirbhaya case was of the view that rape and sexual assault are not merely crimes of passion but an expression of power. The 2013 Amendment brought about substantial changes in the laws for crimes against women, and several new crimes like stalking, harassing the women at the work places, voyeurism, severe punishments for acid throwing and so on were introduced. The Information Technology Act, 2000, describes cyber-crimes in relation to sex and sexuality and has provisions for severe punishment. The POCSO Act was enacted in 2012 to deal with sexual offences committed against children. Recently, important developments have occurred, like decriminalizing the same-sex relationships, striking down adultery as an offence, introducing legislation for transgenders, ensuring human rights for sex workers and so on. A brief account of criminal laws in relation to sex and sexuality is given in this article.